KONSENTRASI EKSTRAK ETANOLIK DAUN PEPAYA (Carica papaya L.) TERHADAP PERUBAHAN WARNA BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS - Purnama, Ryana Budi; Laksitasari, Anindita; Handayani, Fani Tuti; Widyaningsih, Pratiwi Nur; Rahmawati, Dewi; Milla, Dzhofirotul; Artanti, Evania Bellinda; Nahya, Bintan (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Heat-cured acrylic resin is one of the materials used in making denture bases which has the disadvantage that it easily absorbs water and can make discoloration. Papaya leaves (C. papaya L) contain phenolic compounds (C6H6OH-) which can affect the color change of heat-cured acrylic resin. The purpose of this study is to determine the effect of various concentrations of papaya extract on discoloration of the heat-cured acrylic resin denture base. This experimental research is done in vitro at a laboratory using papaya leaf extract (C. papaya L) concentrations of 5%, 10%, and 20%. Thirty two samples of acrylic resin plates were divided into 4 groups, namely the immersion treatment group in papaya leaf extract concentrations of 5%, 10%, and 20%, and the negative control group in the form of aquadest soaking. The color change test was carried out using a UV-visible spectrophotometer. Data was analyzed using the One-Way ANOVA followed by Post-Hoc LSD test. The results of the study showed that there was a very significant difference in the mean value of color change between the treatment groups soaking in papaya leaf extract at concentrations of 10% and 20% and the control group, while at 5% concentration there was no significant difference from the control group. The lowest mean absorbance value was in the distilled water immersion group of 3.341350 ± 0.0942091 and the highest mean absorbance value was in the 20% immersion group of 3.553638 ± 0.0227829. This study concluded that there is an effect of various concentrations of papaya leaf extract on discoloration of the heat-cured acrylic resin denture base. Keywords: Carica papaya L, discoloration, acrylic resin, denture base.